2010
DOI: 10.1007/s10344-010-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent selection of greenness by African elephants in the Kruger-private reserve transboundary region, South Africa

Abstract: Foraging behaviour and habitat selection occur as hierarchical processes. Understanding the factors that govern foraging and habitat selection thus requires investigation of those processes over the scales at which they occur. We investigated patterns of habitat use by African elephants (Loxodonta africana) in relation to vegetation greenness to investigate the scale at which that landscape attribute was most closely related to distribution of elephant locations. We analysed Global Positioning System radiocoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Marshal et al . () have shown that elephants will occupy areas with different levels of primary productivity based on whether the season was wet or dry. Yet without more details on the surveys performed, factors such as these cannot be incorporated into continent‐wide ungulate studies.…”
Section: Discussionmentioning
confidence: 99%
“…Marshal et al . () have shown that elephants will occupy areas with different levels of primary productivity based on whether the season was wet or dry. Yet without more details on the surveys performed, factors such as these cannot be incorporated into continent‐wide ungulate studies.…”
Section: Discussionmentioning
confidence: 99%
“…Used resources were defined as GPS locations of the lions within their respective seasonal Time Local Convex Hull (T-LoCoH) home ranges calculated in Yiu et al (2017) following Lyons, Turner, and Getz (2013), as T-LoCoH excludes locations where the animals explore only occasionally thus did not represent the daily use of resources. Within-home range available resources were defined as random points created within seasonal minimum convex polygon (MCP) home ranges (Marshal et al, 2010;Davidson et al, 2012;DeCesare et al, 2012), as MCP are includes all areas available to that animal in that time period (Northrup et al, 2013). We sampled random points at a ratio of 1:1 to the number of used locations to ensure that the random points representing the available resources were accessible to the animals at the specific spatial and temporal scale (Recio et al, 2014).…”
Section: Habitat Selection Modelling and Model Validationmentioning
confidence: 99%
“…Such variability in food abundance is expected to affect the spatio-temporal patterns of movement, foraging, and habitat use, as seen in African elephants (e.g. Blake 2002, Marshal et al 2010). Total abundance or NDVI that do not reflect food species abundance patterns would, therefore, yield misleading results.…”
Section: Discussionmentioning
confidence: 99%
“…Murwira and Skidmore 2005, Young et al . 2009, Marshal et al 2010, Rood et al 2010, Bohrer et al 2014). However, while NDVI has been found to be a good surrogate of total vegetation biomass/primary productivity in various habitats (savannahs: e.g.…”
Section: Introductionmentioning
confidence: 99%